A little princess - Burnett, Frances Hodgson; Konigsburg, E.L (New York F. Watts, 2007)
Sara Crewe, a pupil at Miss Minchin's London school, is left in poverty when her father dies but is later rescued by a mysterious benefactor
Includes a study guide
Originally published : 1905
Hurg
5 8
Keywords: Great Britain -- History -- Fiction; Orphans -- Fiction; Schools -- Fiction